Mengenal pasti jurang persepsi antara staf pentadbiran & staf akademik untuk meningkatkan keberkesanan pengurusan universiti dan fakulti di institusi pengajian tinggi - Mohd. Nain, Ahmad Shukri; Md. Rasli, Amran; Abd. Majid, Norazman; Muhammad, Faruk (Faculty of Management and Human Resource Development, 2007)
Management and administration in higher learning institutions becoming more complex, facing more demanding expectations from stakeholders, and a more limited financial resources. Hence, the university and faculty administrators must understand their internal environment for an improved sense of identity, purpose , and efficiency. High levels of conflict and tension between the academic staff and administrative staff in higher learning institutions can cause institutional paralysis. However, research in the area remains sparse. This study seeks to identify the levels of conflict and clarify reasons for gaps between academic staff and administrative staff in local higher learning institution. This understanding may allows leadership in these institutions to effectively manage conflict and tension for healthier and more productive internal environment. Using the higher education and organizational study literature domains, questions were formulated to address areas of organisation visions, organisation management, job dimensions, and job satisfactions. A survey was conducted among academic staff and administrative staff in Universiti Teknologi Malaysia, Skudai to explore areas for conflicts found between these two groups. Differences in means were calculated to distinguish the differences of perceptions between academic staff and administrative staff. It was found that perception towards university visions, management, and job dimension issues shows a conflicting viewpoints with academic and administrative staff. It is apparent that many issues contribute to conflict and tensions between them and therefore it is imperative the internal environment of higher education in this country be comprehensively understood.